2006
DOI: 10.1002/hep.21115
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of cardiac proteins is associated with abnormal cardiac chronotropic responses in rats with biliary cirrhosis

Abstract: Acceleration of the heart rate in response to catecholamines is impaired in cirrhosis. In this study, we tested the hypothesis that increased formation of reactive nitrogen species in biliary cirrhosis causes nitration of cardiac proteins and leads to impaired chronotropic function. Bile duct-ligated (rats with cirrhosis) or sham-operated rats were injected daily with either saline, N G -L-nitro-arginine methyl ester (L-NAME), or N-acetylcysteine for 7 days from week 3 to week 4 after surgery. Cardiac chronotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 47 publications
(74 reference statements)
5
36
0
Order By: Relevance
“…Simultaneous elevations in NO and superoxide can result in formation of peroxynitrite, which compromises protein function by formation of nitrotyrosine [35]. It has been demonstrated that nitration of cardiac proteins is associated with abnormal cardiac chronotropic responses in rats with biliary cirrhosis [36]. Our data now show elevated nitrotyrosine levels in the heart of TAAtreated animals within a month after treatment indicating that formation of peroxynitrite and nitrosative stress in the heart is also an early event in conjunction with oxidant stress.…”
Section: Oxidative and Nitrosative Stress In The Heart Precedes Develsupporting
confidence: 56%
“…Simultaneous elevations in NO and superoxide can result in formation of peroxynitrite, which compromises protein function by formation of nitrotyrosine [35]. It has been demonstrated that nitration of cardiac proteins is associated with abnormal cardiac chronotropic responses in rats with biliary cirrhosis [36]. Our data now show elevated nitrotyrosine levels in the heart of TAAtreated animals within a month after treatment indicating that formation of peroxynitrite and nitrosative stress in the heart is also an early event in conjunction with oxidant stress.…”
Section: Oxidative and Nitrosative Stress In The Heart Precedes Develsupporting
confidence: 56%
“…Although this hypothesis is attractive within the context of "cirrhotic cardiomyopathy" (18,61), recent studies have shown that decreased HRV following endotoxin challenge is not related to alterations in cardiac ␤-adrenergic signaling in endotoxemic mice (36). In addition, loss of HRV in a rat model of cirrhosis occurs independently of any impairment in cardiac ␤-adrenergic responsiveness (35).…”
Section: Discussionmentioning
confidence: 99%
“…Peroxynitrite is a reactive oxygen species, formed by the reaction of NO with superoxide anion (O 2Ϫ ), that may inhibit cardiac function through nitration (or S-nitrosation) of cardiac contractile proteins, such as actin (67). In a rat model of bile duct ligated cirrhosis, increased protein nitration in cardiac tissue was associated with reduced chronotropic function (68). In a separate study of L-NAME (NG-L-nitro-arginine methyl ester) and N-acetylcysteine, decreased cardiac nitrotyrosine levels favored normalization of cardiac function and further confirmed the inhibitory effect of nitration.…”
Section: Role Of Nomentioning
confidence: 99%